An Ecological Study of Selected Poems by W. S. Merwin - Abdulateef, Aseel (Al-Adab Journal, 2024)
The American poet W. S. Merwin (1927-2019) is one of the most important enthusiastic ecopoets. He protests against the maladies of modem life which viciously damage our environmental health and causes imbalance in the ecosystem. Merwin makes man aware of the consequences of being out of the natural order, and of making the ecosystem vulnerable to collapse. His ecologically-minded poetry, which is rich with the sublimities of the landscape, profoundly influences man’s ideas about the relation with the other natural creatures, to bridge the gap between man and the Mother earth. He helps man perceive his proper place in the natural order. Industrialization and urbanization toxify man’s bodies and environment. Besides, political crises and wars lead to ecological disasters. The poet artistically embodies these unnatural devastations which threaten the whole planet. His poetry is a call to maintain endangered species of plants and animals. Not only his poetry but also his life are dedicated to protect wilderness which is essential to preserve the human life. Most of his ecological poems spring from the Hawaiian rain forest for which Merwin was fighting to preserve.